2017
DOI: 10.1038/cddiscovery.2017.47
|View full text |Cite
|
Sign up to set email alerts
|

Induction of autophagy by sphingosine kinase 1 inhibitor PF-543 in head and neck squamous cell carcinoma cells

Abstract: Sphingosine kinase 1 (SphK1) overexpressed in head and neck squamous cell carcinoma (SCC) regulates tumor growth. The effects of PF-543, a specific SphK1 inhibitor, on human SCC cells were examined. The proportion of viable cells after PF-543 treatment decreased in a time- and dose-dependent manner, and cell death occurred in SphK1-expressing SCC cells. Flow cytometry analysis revealed that PF-543 induced both necrosis and apoptosis. PF-543 also induced granular accumulation of LC3 and conversion from LC3-I to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…SPHK inhibition, either genetically or pharmacologically, inhibited cell viability and proliferation, followed by the induction of LDH and ROS production. These results are supported by findings obtained by Hamada et al, who reported that SPHK1/2 is involved with cell death, proliferation, ROS production [74]. Furthermore, we observed that SPHKs are involved in inhibiting cancer-mediated inflammation.…”
Section: Discussionsupporting
confidence: 93%
“…SPHK inhibition, either genetically or pharmacologically, inhibited cell viability and proliferation, followed by the induction of LDH and ROS production. These results are supported by findings obtained by Hamada et al, who reported that SPHK1/2 is involved with cell death, proliferation, ROS production [74]. Furthermore, we observed that SPHKs are involved in inhibiting cancer-mediated inflammation.…”
Section: Discussionsupporting
confidence: 93%
“…Autophagy involves intracellular self‐degradation via double‐membrane organelles (autophagosomes), which transfer cytoplasmic material to lysosomes [26,27]. The pharmacological effects of CBD associated with autophagy have been demonstrated in numerous studies [14,20].…”
Section: Discussionmentioning
confidence: 99%
“…In animal studies, intravenous injection of PF543 significantly suppressed HCT-166 xenograft growth while markedly improving mouse survival [ 158 ]. Treatment of oral SCC cells with PF543 at a concentration of 25 ÎŒM reduced cell viability, and induced apoptosis, necrosis, and autophagy, although autophagy promoted cell survival [ 159 ]. At higher concentrations, the inhibitory effects of PF543 on cell proliferation and cell survival may be ascribed to its off-target effects on other cellular enzymes, including SphK2.…”
Section: Inhibitors Of Ceramide- and Sphingosine-metabolizing Enzymentioning
confidence: 99%